The Roles of Xenobiotic Receptors: Beyond Chemical Disposition - Mackowiak, Bryan; Hodge, Jessica; Stern, Sydney; Wang, Hongbing (Drug metabolism and disposition, 2018)
Over the past 20 years, the ability of the xenobiotic receptors to coordinate an array of drug-metabolizing enzymes and transporters in response to endogenous and exogenous stimuli has been extensively characterized and well documented. The constitutive androstane receptor (CAR) and the pregnane X receptor (PXR) are the xenobiotic receptors that have received the most attention since they regulate the expression of numerous proteins important to drug metabolism and clearance and formulate a central defensive mechanism to protect the body against xenobiotic challenges. However, accumulating evidence has shown that these xenobiotic sensors also control many cellular processes outside of their traditional realms of xenobiotic metabolism and disposition, including physiologic and/or pathophysiologic responses in energy homeostasis, cell proliferation, inflammation, tissue injury and repair, immune response, and cancer development. This review will highlight recent advances in studying the noncanonical functions of xenobiotic receptors with a particular focus placed on the roles of CAR and PXR in energy homeostasis and cancer development.